Diversity of ectomycorrhizal hypogeous fungi in the protected area "Tulovska koria" - Slavcho Savev; Dimitаr Kasabdanchev; Teodor Nedelin (Silva Balcanica)
The paper presents results of an assessment of subterranean fungal diversity in the protected area “Tulovska koria”, an endangered forest ecosystem in Bulgaria. High diversity was documented on a relatively small area, consisting of 14 species belonging tо 7 families and two orders. Half of the established species belonged to the genus Tuber (fam. Tuberaceae). Two of the species are of conservation importance and are therefore included in the Red Data Book of Bulgaria. Nine species were confirmed as a part of the natural Bulgarian mycota.